Intervensi Perawatan Luka dengan Irigasi pada Pasien DM Tipe II - Nurapandi, Adi; Rayasari, Fitrian; Anggraini, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to determine the effectiveness of wound care interventions using the irrigation method in type 2 DM patients at Al-Ihsan Hospital Bandung. This research method uses a Quasy Experiment one group pretest and posttest design approach using a random sample of 7 respondents and following operational standards. The results of the study, before and after the intervention, were assessed using the BJWAT Bates-Jensen wound assessment tool to assess whether there was a decrease in the degree of injury or not, from the first session and the second assessment session. The intervention was carried out during 2 wound treatments. From the results of statistical tests, it was found that there was a significant difference in the results of the first assessment and the second assessment before and after wound treatment with irrigation with a p-value of 0.001 (P<0.05). In conclusion, the implementation of wound care interventions in type 2 diabetes patients with irrigation has proven to be effective in helping speed up wound healing, this is proven by reducing the degree or scale of wounds after the intervention. Keywords: Diabetes Mellitus, Wound Care Intervention, Irrigation.